Optimization of electric vehicle's controllers for performance enhancement - Mohammed Essam Farouk Hussein; e; Mohammed El Sayed Ammar; Adel Abdel Moneim Abdullah Al-Samahi; Mohammed Shawky Mohammed Saad (2024)
The aim of this thesis is the exploration of advanced control strategies for optimizing electric vehicles controllers performance based on different optimization techniques, including Proportional Integral Derivative (PID) and Fractional Order Proportional Integral Derivative (FOPID) controllers using different methodologies. Furthermore Fuzzy logic and machine learning controllers such as Artificial Neural Network (ANN) and Reinforcement Learning and Adaptive Neuro Fuzzy Inference System are used. All these controllers are used to optimize the cost function to its$1 (Bminimum value.s
(3GdgOa ef gPg GdCWQhMI gh GSJcTGa GSJQGJjLjGJ GdJMce GdeJbOeI dJMSjf COGA hMOGJ GdJMce aj GdeQcHGJ GdcgQHGFjI HfGkA Ydi JbfjGJ GdJMSjf GdeNJdaI, HeG aj Pdc GdeTJb GdJcGedj GdJfGSHj (B(PID) (3hGdeTJb GdJcGedj GdJfGSHj GdLRFj (B(FOPID) (3HGSJNOGe efgLjGJ eNJdaI, YdGhI Ydi GSJNOGe GdefWb GdVHGHj hhMOGJ JMce GdJYde GdBdi eKd GdTHcI GdYUHjI GdGUWfGYjI (B(ANN) (3hGdJYde GdeYRR hfXGe GdGSJOdGd GdYUHj GdVHGHj GdJcjaj(B. (3jJe GSJNOGe LejY hMOGJ GdJMce gPg dJMSjf OGdI GdJcdaI Edi GdMO GdCOfi dbjeJgGs
Thesis (M.Sc)-Cairo University, 2024.
Bibliography: pages 141-145.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Electric Vehicle's; (3GdeQcHGJ GdcgQHGFjIs; Electric Vehicles -- PID Controller -- FOPID Controller -- Fuzzy Logic Controller -- Machine Learning